Evaluasi dan Rekomendasi Tampilan Website E-Complaint Universitas Brawijaya Pada Perangkat Bergerak Menggunakan Metode Heuristic Evaluation - Wahyu Satriyo Wibowo; Hanifah Muslimah Az-Zahra; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Usability issues of Brawijaya University's E-Complaint website, particularly any of those issues faced by mobile device users due to less responsive display, receive considerable attention because they affect user's perspective on the website. Thus, a usability evaluation was done by applying heuristic evaluation method to fix the issue faced by the users. These experts relied on provided 13 heuristic mobile checklists to conduct the evaluation. Usability assessment was also conducted on the user's side by utilizing System Usability Scale (SUS) and it was complemented with interview with 8 respondents who were categorized into 2 groups: Brawijaya's scholars and general public. The heuristic evaluation highlighted 66 issues in total which were then summarized into 27 issues including issues found during interview with the respondents. Those results were then used for revision. UB's E-Complaint website display improvement was based on the collected guidelines, expert solutions, and user feedback. This improvement lowered the number of issues found by the experts, from 66 into 29 issues with average severity rating of 1,80 (it was previously 2,84). User satisfaction was also improved from SUS score of 44.38 into 72.5 and was supported by positive responses received from the interviews. SUS score indicated that there were some improvements in adjective rating from â€œOKâ€ to â€œGoodâ€, in grade scale from â€œFâ€ to â€œCâ€, and in acceptability from â€œnot acceptableâ€ into â€œacceptableâ€.